Single nucleotide polymorphisms and uses thereof - GARCIA JOSE G N (2022)
A method of identifying a single nucleotide polymorphism (SNP) within a NAMPT promoter associated with an inflammatory condition. Methods of diagnosing and treating inflammatory conditions in a subject are also provided. 一种鉴定与炎症性病症相关的NAMPT启动子内的单核苷酸多态性(SNP)的方法。还提供了诊断和治疗受试者的炎症性病症的方法。